2014
DOI: 10.1007/s00415-014-7446-0
|View full text |Cite|
|
Sign up to set email alerts
|

A 2-year observational study of patients with relapsing-remitting multiple sclerosis converting to glatiramer acetate from other disease-modifying therapies: the COPTIMIZE trial

Abstract: Studies suggest that patients with relapsing-remitting multiple sclerosis (RRMS) who do not benefit from other disease-modifying treatments (DMTs) may benefit from converting to glatiramer acetate (GA). COPTIMIZE was a 24-month observational study designed to assess the disease course of patients converting to GA 20 mg daily from another DMT. Eligible patients had converted to GA and had received prior DMT for 3–6 months, depending on the reasons for conversion. Patients were assessed at baseline and at 6, 12,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…Switching to glatiramer acetate Several trials have evaluated switching to GA from other MS therapies for safety and efficacy reasons [81][82][83]. For patients not responding to first line therapies GA can be offered as an alternative to so-called second line medications if there are concerns of tolerability/adverse events with the latter therapies.…”
Section: Once-daily Formulation In Relapsing-remitting Multiple Sclermentioning
confidence: 99%
See 1 more Smart Citation
“…Switching to glatiramer acetate Several trials have evaluated switching to GA from other MS therapies for safety and efficacy reasons [81][82][83]. For patients not responding to first line therapies GA can be offered as an alternative to so-called second line medications if there are concerns of tolerability/adverse events with the latter therapies.…”
Section: Once-daily Formulation In Relapsing-remitting Multiple Sclermentioning
confidence: 99%
“…For patients not responding to first line therapies GA can be offered as an alternative to so-called second line medications if there are concerns of tolerability/adverse events with the latter therapies. Most studies describe switches from IFNβ-1a or -1b to GA, reporting reductions in mean ARR after switching [81][82][83]. However, in those situations when the shift is due to failure of the previous treatment, results should be interpreted with caution because the regression to the mean phenomenon is a major concern.…”
Section: Once-daily Formulation In Relapsing-remitting Multiple Sclermentioning
confidence: 99%
“…Our study provides further insight into the effect of glatiramer acetate after treatment switch, supporting the improvement in MSrelated fatigue from the 6th month on glatiramer acetate. In addition, a recently published study has shown greater fatigue reduction in patients switching their immunomodulatory therapy as a result of lack of efficacy compared to those who switched due to adverse events [18] . These findings warrant further research to maximize fatigue benefits and prolong them in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue decrease over this first year was even sustained after 2 years of glatiramer acetate and was predicted by fatigue improvements achieved 6 months after starting the treatment [17] . Although similar reductions seem to occur in patients previously treated with other immunomodulatory/immunosuppressive therapies [17,18] , the evidence available is still limited, less consistent [16,17] , and potentially affected by secondary causes of fatigue such as depressive symptoms [16][17][18] .…”
Section: Introductionmentioning
confidence: 91%
“…These Also Natalizumab, the first monoclonal antibody to treat highly active multiple sclerosis, with studies demonstrating better efficacy on disease activity and disability progression compared to interferons (e.g., Ref. 37,38 ), demonstrated in a reanalysis of the SENTINEL 39 and AFFIRM 40 phase III studies that treatment with Natalizumab reduced the risk of confirmed progression of cognitive deficits by 43% in comparison with a placebo. 41 The same applies to the STRATA extension study, where cognitive impairments were assessed monthly using the SDMT and MSNQ until the end of the study after 48 weeks.…”
Section: Immunomodulatory Treatments and Cognitionmentioning
confidence: 99%